Location-Based Information Systems: Developing Real-Time Tracking Applications - Labrador, Miguel A; Perez, Alfredo J; Wightman, Pedro M (Chapman & Hall/CRC computer and information science series, 2010)
Drawing on the authors' more than six years of R&D in location-based information systems (LBIS) as well as their participation in defining the Java ME Location API 2.0, Location-Based Information Systems: Developing Real-Time Tracking Applications provides information and examples for creating real-time LBIS based on GPS-enabled cellular phones